Semi‐Transparent Organic Photovoltaics: Sequential Deposition of Donor and Acceptor Provides High‐Performance Semitransparent Organic Photovoltaics Having a Pseudo p–i–n Active Layer Structure (Adv. Energy Mater. 13/2021). Issue 13 (8th April 2021) - Wang, Hao‐Cheng; Cheng, Pei; Tan, Shaun; Chen, Chung‐Hao; Chang, Bin; Tsao, Cheng‐Si; Chen, Li‐Yin; Hsieh, Chung‐An; Lin, Yu‐Che; Cheng, Hao‐Wen; Yang, Yang; Wei, Kung‐Hwa
Abstract : In article number 2003576, Kung‐Hwa Wei and co‐workers demonstrate that semi‐transparent organic photovoltaics with a sequential deposited (SD) active layer—individually deposited polymer donor layer and a small‐molecule acceptor layer—forming pseudo p–i–n structures have larger power conversion efficiency and transmittance values than those for the devices with bulk heterojunction (BHJ) structures, and the enhancements for SD versus BHJ devices increase with the decreasing active layer thickness.